THERMAL ZONE MODELLING IN GEOTHERMAL SYSTEM USING GEOTEMP - SHOFIYA KURNIAWATI (NIM : 10212056), ANA
With the increasing of population, industrialization, and the improvement standard of living, there has been a continuous increase in consumption of energy. Geothermal is one of the alternative energy which has been catering the requirement of world energy. One of the fundamental parameters controlling the viability of any geothermal project is the temperature of the reservoir. The reservoir temperature is directly related to the physical parameters such as the thermal properties of the rock and formation chemistry and dynamics. Those parameters could determine the potential of geothermal energy on some areas. On this research, GeoTemp is used to analyze the geothermal energy potential. The GeoTemp software defines a framework for thermal regime identification, analyzing and modeling wireline logging data, and discrete temperature measurement. The expected results are temperature distribution and thermal characteristic on subsurface.